Stigmatic ROS: regulator of compatible pollen tube perception?. (October 2021) - Zhou, Liang-Zi; Qu, Li-Jia; Dresselhaus, Thomas
Abstract : Accurate communication at the stigma surface is required to promote plants' own pollen and reject foreign pollen. Liu et al . have now discovered an autocrine signaling pathway at the surface of arabidopsis stigmatic papillae, accumulating ROS. Downregulation of ROS production via an antagonistic peptide from the pollen coat promotes pollen hydration and germination.